2010
DOI: 10.1118/1.3312435
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction using a CdZnTe‐based computed tomography system: Comparison to flat‐panel detectors

Abstract: Purpose: Although x-ray projection mammography has been very effective in early detection of breast cancer, its utility is reduced in the detection of small lesions that are occult or in dense breasts. One drawback is that the inherent superposition of parenchymal structures makes visualization of small lesions difficult. Breast computed tomography using flat-panel detectors has been developed to address this limitation by producing three-dimensional data while at the same time providing more comfort to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 44 publications
1
80
0
Order By: Relevance
“…It was found that the contrast-to-noise ratio was increased by 1.35 times, while the dose can be reduced by 52.05%, when compared to flat panel systems. 21 The ability to identify and quantify specific materials adds another dimension to the imaging system. In a single CT scan using the CZT system, one obtains both the standard CT data and the additional information about the amount of material present in a particular image region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the contrast-to-noise ratio was increased by 1.35 times, while the dose can be reduced by 52.05%, when compared to flat panel systems. 21 The ability to identify and quantify specific materials adds another dimension to the imaging system. In a single CT scan using the CZT system, one obtains both the standard CT data and the additional information about the amount of material present in a particular image region.…”
Section: Discussionmentioning
confidence: 99%
“…Current CZT detector technology allows for five to eight user-selectable energy bins. 16,18,21,28 Here, our simulated detector could resolve the spectrum into five energy bins. The sinogram for each energy bin is calculated by…”
Section: Iie System Geometry and X-ray Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in solid state semiconductor materials allow photon-counting and energy discriminating imaging detectors to be used in a breast CT system to produce higher quality images. [1][2][3][4][5][6][7][8][9] Cadmium zinc telluride (CZT) single crystal detectors have been investigated and implemented as x-ray detectors in current breast CT systems. These systems use CZT due to its large effective atomic number (49.6), high mass density (5.8 g/cm 3 ), and higher quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, technical improvements in CT detector design, which are now capable of event by event counting, will markedly reduce the radiation burden, making Coronary CT Angiography more attractive. 2 Given the demand for 'newer' and 'better' by the referring clinicians, it is time to take the plunge, and for Nuclear Physicians to make the case for higher quality patient care, offered by well-established PET/CT technology.…”
mentioning
confidence: 99%